2011
DOI: 10.1016/j.jep.2010.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Renal toxicity caused by oral use of medicinal plants: The yacon example

Abstract: The renal damage was associated with increased blood glucose levels after prolonged oral administration of the AE. This observation suggested that the hypoglycaemic effect observed after treatment for 30 days in an earlier study is reversible and was likely the result of renal injury caused by the toxicity of yacon. Because STLs were detected in both AE and LRE, there is strong evidence that these terpenoids are the main toxic compounds in the leaves of the yacon. Based on our results, we do not recommend the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 22 publications
1
22
0
6
Order By: Relevance
“…Such results were also obtained with ethanoic extract of the plant leaves (Nwinyi, 2009). By cons, a chronic nephrotoxicity was observed both biochemically (increased blood urea and creatinine) and histologically (hydropic degeneration, tubular atrophy, impaired glomeruli and infiltration of inflammatory cells) with aqueous extracts of Mentha spicata and Smallanthus sonchifolius, which are anti diabetic plants (Akdogan, 2003;Oliveira, 2011). Transaminases AST and ALT have declined slightly on day 14 indicating no liver cells lysis.…”
Section: Discussionmentioning
confidence: 99%
“…Such results were also obtained with ethanoic extract of the plant leaves (Nwinyi, 2009). By cons, a chronic nephrotoxicity was observed both biochemically (increased blood urea and creatinine) and histologically (hydropic degeneration, tubular atrophy, impaired glomeruli and infiltration of inflammatory cells) with aqueous extracts of Mentha spicata and Smallanthus sonchifolius, which are anti diabetic plants (Akdogan, 2003;Oliveira, 2011). Transaminases AST and ALT have declined slightly on day 14 indicating no liver cells lysis.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several phytochemical and pharmacological studies (Aybar et al, 2001;Genta et al, 2010;Valentová et al, 2005) of yacon leaves have been conducted in the recent decades. Although there is sufficient evidence of their potential activity in the treatment of hyperglycaemia and its complications, there is still disagreement about their safe use and the appropriate therapeutic dose (de Oliveira et al, 2011;Fernandes et al, 2005;Genta et al, 2010;Siriwan et al, 2011). In the current study, we demonstrated that both a 10% decoction of yacon leaves and enhydrin have a safety margin in Wistar rats at doses in which was demonstrated hypoglycaemic effects.…”
Section: Discussionmentioning
confidence: 52%
“…In a recent work, de Oliveira et al (2011) showed that prolonged oral administration (90 days) of extracts of S. sonchifolius was associated with kidney damage and attributed it to the presence of sesquiterpene lactones in the extract. However, the analysis of the results presented by these authors shows that the aqueous extract of yacon leaves triggers biochemical and histopathological changes when administered at high doses (100 mg/kg).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, no toxic effects were observed when a root extract was administered each day intragastrically at doses of 2000 mg•Kg −1 during a 4-month period [46]. It should be mentioned, however, that a long treatment (90 days) with hydromethanolic extracts of yacon leaves induced substantial renal toxicity [47].…”
Section: Discussionmentioning
confidence: 95%